A call for solidarity and progress: efforts in development ethics bridging both theory and practice based within North America - Schwenke, Chloe (Journal of global ethics, 2024)
This article shares lessons-learned by the Center for Values in International Development (C4V) over nearly five years. It notes entrenched resistance by the US Agency for International Development (USAID) of any definition of ‘ethics’ beyond legal and regulatory compliance with government financial, procurement, and programming standards. Among practitioner organizations and firms, incorporation of international development ethics is generally viewed as naïve, out of touch with the highly competitive development ‘market’, and hence unnecessary. The article ends with a call to action to coordinate and create mechanisms, provide funding and forums, and significantly improve collaboration between international development ethicists in academic circles, with international development and humanitarian response practitioners.